“…and How Are the Kids?” Psychoeducation for Adult Patients With Depressive and/or Anxiety Disorders: A Pilot Study - Potijk, Marieke R.; Drost, Louisa M.; Havinga, Petra J.; Hartman, Catharina A.; Schoevers, Robert A. (Frontiers in Psychiatry, 2019)
Abstract Depressive and anxiety disorders are highly prevalent and form a substantial burden for individuals and their family members. A recent study showed that approximately two-thirds of the children of patients with severe depressive and/or anxiety disorders develop one of these disorders themselves before 35 years of age. In the Netherlands, various preventive interventions are available for children of parents with mental illnesses. However, the actual reach of interventions is small (<1% of all children participate). A major barrier appeared to be parents’ hesitancy to let children participate in preventive programs. In order to address this barrier, we designed a pilot study to implement a psychoeducation program on parenting and mental illnesses. The main aim of this study was to investigate how a preventive family-focused approach can be embedded in routine adult psychiatric care. The pilot started in April 2017 and has ended in September 2018. It was conducted in the University Center Psychiatry (UCP) in Groningen, The Netherlands. This article describes the implementation process so far. The main intervention was a monthly organized group-psychoeducation called ‘parenting and a mental illness’, which could be attended by parents currently treated in the UCP. In 18 months, implementation activities were divided in four phases; 1. Creating awareness, 2. Adoption of the intervention, 3. Implementation and evaluation, and 4. Continuation phase. The program development process was evaluated using both qualitative and quantitative data. Based on the pilot study we were able to make recommendations for the further implementation of this approach so that more parents can be reached in future. Further study with follow-up activities is needed to measure the effects of the psychoeducation, for instance on parenting functioning and the quality of the parent-child interaction.